Heterozygous antithrombin deficiency improves in vivo haemostasis in factor VIII-deficient mice - Bolliger, Daniel; Szlam, Fania; Suzuki, Nobuaki; Matsushita, Tadashi; Tanaka, Kenichi A. (Thrombosis and Haemostasis, 2010)
Decreased levels of factor VIII (FVIII) limit the amount of thrombin generated at the site of injury, but not the rate that thrombin is neutralised by antithrombin (AT). We hypothesised that FVIII-deficient mice with heterozygous AT deficiency will demonstrate increased thrombin generation and therefore less in vivo bleeding compared to FVIII-deficient mice with normal AT levels. Therefore, we performed tail bleeding experiments in wild-type (WT), heterozygous AT deficient (AT+/-) mice, FVIII-deficient (FVIII-/-) mice, and FVIII-deficient mice with heterozygous AT deficiency (FVIII-/-/AT+/-). Amount of bleeding was assessed by measuring absorbance of haemoglobin released from lysed red blood cells collected after tail transection. In addition, we measured thrombin generation, activated partial thromboplastin time (aPTT), and AT activity in plasma from the different mice groups. Tail bleeding was significantly reduced in FVIII-/-/AT+/- mice compared to FVIII-/- mice. On the other hand, there was no difference in tail bleeding between AT+/- and wild-type mice. Thrombin generation was dependent on the mice geno-type, and increased in the following order: FVIII-/- < FVIII-/-/AT+/- < WT < AT+/-. The aPTT was not influenced by reduced AT activity (i.e. AT+/- genotype), but was significantly prolonged in FVIII-/- and FVIII-/-/AT+/- mice. Using FVIII-deficient mice as an in vivo murine model of reduced thrombin generation, we demonstrated that moderately reduced AT levels increase thrombin generation and decrease bleeding after traumatic tail vessel injury. In agreement with congenital thrombotic conditions, our data elucidate that bleeding phenotypes can be modulated by the balance between procoagulant and anticoagulant proteins.
Keywords: Antithrombin; thrombin generation; coagulation factors; haemophilia